2020
DOI: 10.1177/0047287520966392
|View full text |Cite
|
Sign up to set email alerts
|

To Guilt or To Vacation: Constraining Effects of Guilt on Vacation Decisions

Abstract: Annual usage of paid leave in America has been declining although employees are granted more time off than before. This study proposes that taking paid leave for a vacation is perceived as a violation of workplace norms, which could partly explain this phenomenon. This violation is presumed to pose a threat to an employee’s social self at work. The accompanying guilt from such a threat is hypothesized to lead to lower vacation intention and more reparative actions (e.g. apologizing and decreasing vacation leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 101 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…First-time cannabis tourists mentioned three main types of perceived constraints (Figure 1), including three sub-dimensions of intrapersonal constraints: first, tourists' anticipated guilt (i.e. about engaging in cannabis tourism) was associated with potentially violating their personal standards (Huhmann and Botherton, 1997); this concept has been widely employed in tourism studies involving advertising (Soscia et al, 2019), tourist behaviour, such as in eco-tourism (Mkono et al, 2020), and vacation decisions (Tan and Li, 2020). However, only one study (Wen and Qi, 2020) identified tourists' anticipated guilt as an intrapersonal travel constraint for cannabis tourists visiting overseas destinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-time cannabis tourists mentioned three main types of perceived constraints (Figure 1), including three sub-dimensions of intrapersonal constraints: first, tourists' anticipated guilt (i.e. about engaging in cannabis tourism) was associated with potentially violating their personal standards (Huhmann and Botherton, 1997); this concept has been widely employed in tourism studies involving advertising (Soscia et al, 2019), tourist behaviour, such as in eco-tourism (Mkono et al, 2020), and vacation decisions (Tan and Li, 2020). However, only one study (Wen and Qi, 2020) identified tourists' anticipated guilt as an intrapersonal travel constraint for cannabis tourists visiting overseas destinations.…”
Section: Discussionmentioning
confidence: 99%
“…, 2019), tourist behaviour, such as in eco-tourism (Mkono et al. , 2020), and vacation decisions (Tan and Li, 2020). However, only one study (Wen and Qi, 2020) identified tourists' anticipated guilt as an intrapersonal travel constraint for cannabis tourists visiting overseas destinations.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on consumer travel behavior has accumulated over the last decade (Backhaus et al, 2023;Dryhurst et al, 2020;So¨nmez & Graefe, 1998;Tan & Li, 2021;Verplanken et al, 1994), knowledge about consumer travel reduction is still incomplete, and its determinants, especially, require further attention. A review of the literature on consumer travel reduction shows that there are conceptual (e.g., Go¨ssling & Dolnicar, 2023) and empirical (Davison et al, 2014;Kazeminia et al, 2015;McDonald et al, 2015) studies.…”
Section: Consumer Touristic Travel Reductionmentioning
confidence: 99%
“…Following the theory of planned behavior (Ajzen, 1991), social pressure to behave in a socially approved way is a key predictor of both the attitude–behavior relationship (Fishbein & Yzer, 2003) and behavioral intentions (Ajzen, 1991). Studies in the field of tourism have shown that social norms or social risks can have a significant effect on consumer travel decisions (Davison et al, 2014; Doran & Larsen, 2016; Tan & Li, 2021). Doran and Larsen (2016) discovered that social norms positively predicted the choice of ecological travel options.…”
Section: Hypothesesmentioning
confidence: 99%
“…With tourism consumption widely conceptualized as an evolving, temporal five-phase process that commences with anticipation and travel planning and concludes with post-trip recollection (Clawson & Knetsch, 1966), each phase is arguably unique in its elicitation of NEs. To illustrate, Tan and Li (2021) demonstrated that guilt can constrain employees from taking paid time off for a vacation, which corresponds with the travel planning stage. Meanwhile, Li and Chan (2022) revealed that guilt, regret and shame were experienced by Chinese diaspora tourists during visits of their ancestral homes.…”
Section: About Negative Emotionsmentioning
confidence: 99%